Documentation of Historic Buildings For Their 3D Reconstruction In A Digital Cultural Heritage Management System - Chroni, Athina; Georgopoulos, Andreas (Technical Annals, 2022)
Being at the crossway of trade routes, Ioannina, in northwestern Greece, has known overtime an economic and spiritual flourishment reflected in the city’s urban web, which has, unfortunately, undergone major alterations. Focusing on the city’s Post-Byzantine period, starting in 1430, for tracing its pluralistic physiognomy, studying the osmosis of its three cultures, Christian, Jewish and Muslim, and figuring out the related cultural palimpsest, still surviv-ing in the collective memory of the city, has been the great challenge of IASIS Postdoctoral Research Project.1 Extensive documentation of various origin, dynamic and combined interpreta-tion and processing of multiple data, cross-checking of the detected infor-mation, have formed the basic principles of IASIS project development. The specific paper forms the first part of Hagia Paraskevi Christian Byzantine Monastery-Namaz Giyah Muslim Mosque-Perifereia Hellenic State Adminis-trative Building cultural landmarks’ integrated management, i.e., the part on the landmarks’ integrated documentation in the framework of IASIS Postdoctoral Research Project. [35, 36]